Numerical Simulation on Residual Stress Field of Flat-Topped Laser Oblique Shocking of Ni-Based Alloy GH4169 - Xiangming Qu; Yongkang Zhang; Jun Liu (Advances in Materials Science and Engineering)
This paper is based on laser shock peening (LSP) system with a flat-topped beam, using robot simulation software to determine the oblique shock angle of different areas of a certain turbine disk mortise. Three-dimensional finite element analysis was used to study residual stress field of Ni-based alloy GH4169 under flat-topped laser oblique shocking. The effects of different laser energy and different shocking number on residual stress field of Ni-based alloy GH4169 of LSP were studied. Three-dimensional finite element analysis used super-Gaussian beam distribution to construct spatial distribution model of shock wave induced by LSP. The simulation results were in good agreement with the experimental results. The research results will provide a theoretical basis for LSP of certain turbine disk mortise.